La prensa anarquista española en Francia durante la reunificación de la CNT (1960-1965) y su repercusión en las relaciones bilaterales Francia-España - Miguel Morán Pallarés (Cahiers de Civilisation Espagnole Contemporaine)
After the end of the Spanish Civil War, Spanish anarchists were forced into exile, clandestinity and repression. Despite initial tolerance on the part of the French authorities, pressure from the Francoist government regarding the exiles intensified during the 1950s. Between 1960 and 1961 the CNT completed its reunification process, reactivating armed and propaganda actions against Franco. Based on the critical study of the Spanish libertarian publications of the exile and the documentation from international archives, this article aims to show the evolution of the Spanish anarchist press in the French exile between 1960 and 1965, the prohibitions and obstacles to which had to face in terms of its dissemination, as well as the importance that factors related to the respective French and Spanish government interests in matters of security had in its existence, and its impact as a relevant issue in the evolution of bilateral diplomatic relations between both countries.